Hubungan Status Gizi, Kepatuhan Komsumsi Tablet Fe Dan Pemeriksaan Kehamilan (Anc) Dengan Kejadian Anemia Pada Ibu Hamil Di Puskesmas Tebing Gerinting Indralaya Tahun 2024 - Safitri, Shindy; Erma Puspita Sari; Rini Gustina sari; Fika Minata Wathan (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Anemia is a condition where the red blood cells do not meet the physiological needs of the body. Anemia is commonly experienced by women, particularly due to iron deficiency. There are various factors that contribute to anemia, including external factors such as ANC visits, iron supplement tablets, healthcare personnel, and the environment. Internal factors include age, occupation, education, childbirth history, economic status, nutritional status, and family planning history. The aim of this study is to determine the relationship between nutritional status, adherence to iron tablet consumption, and pregnancy check-ups. This research uses a cross-sectional approach, conducted at Tebing Gerinting Health Center, Indralaya Selatan, Ogan Ilir from June 18 to June 30, using univariate and bivariate analysis. The results show that out of a population of 413, 80 respondents were selected, with 53 respondents (66.3%) experiencing anemia and 27 respondents (33.8%) not experiencing anemia. Most of the respondents (34 or 77.3%) had poor nutritional status, 47 respondents (81.0%) were non-compliant with iron tablet consumption, and 46 respondents (79.3%) had incomplete pregnancy check- ups, all of whom experienced anemia. Based on the chi-square test, it was found that there was a significant relationship between nutritional status and anemia occurrence in pregnant women, with a p-value of 0.039. The study concluded that there is a significant relationship between adherence to iron tablet consumption and anemia occurrence in pregnant women, with a p-value of 0.000, and between pregnancy checkups and anemia occurrence, with a p- value of 0.000. Therefore, there was a simultaneous relationship between nutritional status, adherence to iron tablet consumption, and pregnancy check- ups with anemia occurrence in pregnant women. The study recommends increasing public awareness of health, particularly among pregnant women.